Agglomeration and Economic Growth: A Scoping Review of Socioeconomic Conflicts and Policy Implications - Putra Cahyono, Jordan (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2024)
This scoping review aims to synthesize existing research on the relationships between economic agglomeration, social-economic change, and their impacts on economic growth, with a focus on identifying key conflicts and policy issues. The study employs a comprehensive literature search using databases such as Scopus, Web of Science, and Google Scholar, targeting peer-reviewed articles published in the last decade. The review process entails a meticulous examination and synthesis of selected sources, with the findings then organized into a coherent narrative review. The analysis yielded several key themes, including a positive correlation between economic agglomeration and growth, the development of specialized infrastructure and human capital, and the facilitation of knowledge spillovers. Nevertheless, the review also identifies potential adverse consequences, including the displacement of local communities, the intensification of income inequality, and the burden on public services. The study concludes by emphasizing the necessity of carefully designed policy interventions to ensure sustainable and inclusive economic growth, addressing the concerns of all stakeholders involved in the complex dynamics of economic agglomeration and social-economic change in a manner that is both equitable and effective.